2009
DOI: 10.1645/ge-1760.1
|View full text |Cite
|
Sign up to set email alerts
|

Helminth Parasites From the Stomach of Conger Eel, Conger conger, From Madeira Island, Atlantic Ocean

Abstract: Geographic variations in the diversity and prevalence of helminth parasites of fish can provide important clues as to the relatedness of fish populations. In the present work, the stomachs of 64 conger eels, Conger conger, collected during 1999 and 2000, were examined for the presence of parasites. Four fish were infected with L3 stages of the nematode Anisakis simplex s.l. (Anisakidae), 1 with the nematode Cristitectus congeri (Cystidicolidae), 1 with the acanthocephalan Rhadinorhynchus pristis, 17 with postl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While Sanmartin et al 12 did not reported Lecithochirium fusiforme in their study carried out in North-west Spain. A higher prevalance of infection was found by Costa et al 1 in Portugal coasts of Atlantic Ocean and by Culurgioni et al 5 in Italian waters. In this study, Lecithochirium fusiforme was seen to be the most abundant in all species parasites of conger eel.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While Sanmartin et al 12 did not reported Lecithochirium fusiforme in their study carried out in North-west Spain. A higher prevalance of infection was found by Costa et al 1 in Portugal coasts of Atlantic Ocean and by Culurgioni et al 5 in Italian waters. In this study, Lecithochirium fusiforme was seen to be the most abundant in all species parasites of conger eel.…”
Section: Discussionmentioning
confidence: 66%
“…Prosorynchus crucibulum were already detected in various infection rates in different areas of Mediterranean 1,2,5 . It was seen with a prevalance of 11.54% and mean intensity of >25.…”
Section: Discussionmentioning
confidence: 98%
“…In this respect a survey of parasites of the conger eel, C. conger, from Madeira Archipelago, found that some parasites were more abundant in deeper waters. For example the postlarvae of the trypanorhynch Sphyriocephalus tergestinus Pintner, 1913 and the hemiurid digenean Lecithochirium grandiporum (L. fusiforme Lühe, 1901) (Rudolphi, 1819) Lühe, 1901, occurred in waters below 400m deep, whereas the digenean L. musculus (Looss, 1907) Nasir & Diaz, 1971, was present in conger eels only at depths of 200-300m [54]. In the mesobathyal region, fish and crustaceans are the preferential prey, thus explaining the presence of S. tergestinus in deeper waters.…”
Section: Transmission Food-web Dynamics and Geographic Distribution mentioning
confidence: 99%
“…In the deep water realm trypanorhynchs of the families Aporhynchidae, Gilquinidae and larval tetraphyllideans are the most common cestodes infecting fishes and sharks [18,40,47,48]. Nevertheless, trypanorhynchs of the families Tentaculariidae and Sphyriocephalidae, common parasites of epipelagic and mesopelagic fishes, were additionally found in the black-scabbard fish and the conger eel [9,17,54]. This reflects the feeding behaviour of the fish hosts, which undergo extensive vertical migrations [11,54].…”
Section: Transmission Food-web Dynamics and Geographic Distribution mentioning
confidence: 99%
See 1 more Smart Citation